Linked Data for Archives - Niu, Jinfang (Archivaria, 2016)
Based on the investigation of a number of projects that have implemented linked data for archival materials, this article reports on the current status of archival linked data and discusses the impact of linked data on archival description and archival information discovery. The author argues that although the archival community is still in the early stage of linked data implementation, the usage of linked data demonstrates great potential for improving archival description and information discovery. Specifically, the author argues that linked data will enrich archival description by making it increasingly interoperable and granular and make archival information discovery more powerful through the ability to directly answer user questions. RÉSUMÉ En se basant sur l’examen d’un nombre de projets qui ont mis en oeuvre les données liées pour le matériel d’archives, cet article présente l’état actuel des données liées archivistiques et explore leur impact sur la description et sur la découverte de l’information archivistique. L’auteur soutient que malgré le fait que la communauté archivistique est toujours aux tout débuts de la mise en oeuvre des données liées, son utilisation fait preuve d’un potentiel important dans l’amélioration de la description archivistique et la découverte de l’information. Plus spécifiquement, l’auteur affirme que les données liées enrichiront la description archivistique en la rendant davantage interopérable et granulaire, faisant en sorte que la découverte de l’information archivistique deviendra plus puissante par sa capacité de répondre directement aux questions des utilisateurs.